Commentary on the article “Video-assisted preperitoneal repair of parastomal hernia” of Andrzej Jamry - Marek Szczepkowski (Videosurgery and Other Miniinvasive Techniques)
It was with great interest that I read the articletitled “Video-assisted preperitoneal repair of parastomalhernia” published in Videosurgery and otherminiinvasive techniques [1].